Προτεστάντες ιεραπόστολοι στην καθ'ημάς ανατολή, 1819-1914: Η δράση της American board - Κισκήρα, Κωνσταντίνα Π. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
The missionaries of the American Board of Commissioners for Foreign Missions were the Americans who pioneered the propagation of the “American dream” in the Middle East, the cradle of ancient civilizations. Their endeavors in the religious field, from 1829 to 1844 in the newly constituted state of Greece, and from 1819 to 1930 in the territories of the Ottoman Empire, largely in Asia Minor, bore little fruit. In two other areas, however, education and publishing on the one hand and humanitarian work on the other, their efforts proved more successful. Although most of their educational work, in particular, was brought to an end by the events of the First World War, some missionaries did stay on in the Middle East, collaborating now with the semi-official humanitarian organization Near East Relief, throughout the first decades of the twentieth century. In its attempts to “Westernize” Ottoman society, the American Board had a serious rival in the Catholic Church. In the early years of American missionary settlement in the Empire, Catholic propaganda would often play a part in fomenting widespread persecution launched by the Greek Orthodox and Apostolic Armenian Patriarchates against the American missionaries (especially in the years 1836-1839). At the end of the day, however, the American Board missionaries not only remained to witness the fall of the Ottoman Empire, but actually contributed to the fragmentation of Ottoman society, helping to found in 1850 yet one more millet, the Protestants, within an Empire already highly diverse in cultures and peoples. There is no doubt that throughout the many years of their presence in the Empire the American missionaries represented a distinct social unit contributing in its way to the “unorthodox” westernizing of both Christian and Muslim subjects. After the Crimean War, in particular, and the Reform Edict of 1856, when the missions began to advance unchecked through the provinces of the Empire, many regions, especially in the Asian provinces, served an apprenticeship in American culture. It was at this period that the work of the American Board began to grow more rapidly, reaching a peak of activity after the treaty of San Stefano and the Congress of Berlin until the close of the century (1879-1895). The American Board missionaries skillfully took advantage of the diplomatic isolation of Russia which followed the Congress of Berlin to launch their own proselytizing propaganda among the Greeks of Asia Minor who had relied until then on Russian protection. (Until then the Americans’ efforts had enjoyed success only among the Armenian and Bulgarian communities). Thus most of the small Greek Evangelical communities in Asia Minor date from the years following 1879-1880. Today, in the small Macedonian town of Katerini, there is still to be found a tiny Evangelical community composed of the descendants of the largest (300 registered members) of the Greek Evangelical communities in Asia Minor: that of Ordu (Kotyora) on the coast of the Black Sea. In the areas of education, publishing and humanitarian work, the activities of the missionaries enjoyed sometimes spectacular success, for it was in these areas that they were serving the needs of all the ethnic groups within the culturally diverse Empire. This was especially so after the end of the 19th century, when the secularization of Ottoman society was well under way and the American missionaries’ religious zeal had cooled from its earlier intensity. Of particular significance was the role of the missionaries in the creation of a westernized middle class, mainly in the interior of Asia Minor, where the Americans operated properly taught high schools for both boys and girls (Colleges). What was original about these schools’ objectives was that they served the actual needs of local social reality. The work of the missionaries of the American Board constitutes a new field of study for scholars researching Asia Minor in the last century. Among the many documents of human geography left us by the missionaries, of particular interest are the early records of the founders of the Mission stations (1823-1870). These are usually reports in the form of travelers’ journals, drawn up on the instructions of the American Board. They contain geographical descriptions of the region and accounts of the culture and society of the various groups inhabiting it, as well as offering statistical evidence allowing a more systematic study of social structure. The large number of journeys undertaken by the missionaries and the extent of ground they covered mean that their accounts are hard to match from other sources, and often, in fact, unique. This is why study of these records is proving so valuable for research into the human geography of the Asia Minor region Because the archive material bequeathed by the missionaries and by their official periodical, the Missionary Herald, has until now scarcely been used in research into Modern Greek History, the Director of the Center for Asia Minor Studies, Professor P. Kitromelides and the Professor of Turkish Studies at the University of Crete, E. Zachariadou, have included the study of the American Board’s activities in Asia Minor in the new research program of the Center for Asia Minor Studies.